Environmental Education in the Vision of Public Managers and Rural Producers in the Municipality of Palmeira das Missões/RS - Jeferson Rosa Soares; Luis Roberval Bortoluzzi Castro; Dione Iara Silveira Kitzmann (Universidade Federal do Norte do Tocantins, 2020)
The present work had as objective to understand the vision of public managers and rural producers in the municipality of Palmeira das Missões/RS in relation to the practice of Environmental Education (EA) in Areas of Permanent Preservation of Arroio Macaco, through the theoretical component of Environmental Education Critical and Transformative. The relevance of this understanding involves the need to emerge and / or enhance the perception of managers and farmers about the EA of their meanings. The methodology was based on: documental analysis, direct observation in loco, semi-structured interviews. The case study was carried out involving 18 subjects, who expressed their understanding about what they mean by Environmental Education, if it helps to comply with the Terms of Conduct Adjustment and if they participated in courses related to Environmental Education. The collected data were submitted and interpreted through the discourses (categorical context) of those involved, creating categories (thematic category) through Content Analysis. The main difficulties encountered were the lack of information on Environmental Education and the lack of courses by the majority of those involved. It is hoped that the proposed reflections will promote further discussions focusing on Critical Environmental Education, between Managers, Producers and the Community as a whole.